Occurrence of two deadly lepiotas in Western Ghats of Kerala - Vrinda, K B; Pradeep, C K; Varghese, Shibu P; Thomas, Mathew V (Mushroom Research, 2011)
Lepiota brunneoincarnata and Lepiota subincarnata are reported as dangerously poisonous mushrooms containing deadly amatoxins.Â  Complete descriptions of these are provided based on collections from Kerala.